External evaluation of mobile phone technology-based nutrition and agriculture advisory services in Africa and South Asia: Mobile phones, nutrition, and health in Tanzania: Quantitative endline report - Gilligan, Daniel O.; Hidrobo, Melissa; Palloni, Giordano; Tambet, Heleene (Institute of Development Studies, 2020)
The mNutrition initiative is a five-year global programme supported by the UK Foreign, Commonwealth and Development Office (FCDO), organised and supported by Groupe Spéciale Mobile Association (GSMA), and implemented by in-country mobile network operators (MNOs) and third-party providers, which aims to use mobile technology to improve the health and nutritional status of children and adults in low- ncome countries around the world. mNutrition is implemented through existing mAgri and mHealth programmes in 12 countries throughout sub-Saharan Africa and South Asia. The nutrition content aims to promote behaviour change around key farming practices and around dietary and child feeding practices that are likely to result in improved nutritional health within a household. The mNutrition intervention that is the focus of the evaluation in Tanzania, and of this report, is an integrated service that combines an existing short message service (SMS)-based health communication campaign targeting pregnant women and mothers of young children, known as ‘Healthy Pregnancy, Healthy Baby’ (HPHB), with approximately 120 nutrition-focused SMS messages in Swahili. The combined service sends out SMS messages timed to the stage of pregnancy or age of the child. The service is designed to provide relevant information for pregnant women and children up to the age of five in order to affect beliefs and behaviours in key nutritionrelated areas—including infant and young child feeding (IYCF) and women’s dietary diversity—in recipient households